2013
DOI: 10.1186/2051-1426-1-21
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-17-92 enhances anti-tumor activity of T-cells transduced with the anti-EGFRvIII chimeric antigen receptor in mice bearing human GBM xenografts

Abstract: BackgroundExpression of miR-17-92 enhances T-cell survival and interferon (IFN)-γ production. We previously reported that miR-17-92 is down-regulated in T-cells derived from glioblastoma (GBM) patients. We hypothesized that transgene-derived co-expression of miR17-92 and chimeric antigen receptor (CAR) in T-cells would improve the efficacy of adoptive transfer therapy against GBM.MethodsWe constructed novel lentiviral vectors for miR-17-92 (FG12-EF1a-miR-17/92) and a CAR consisting of an epidermal growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 49 publications
4
73
0
Order By: Relevance
“…Gene sequence data for the third-generation CAR was kindly provided by Dr Carl June (University of Pennsylvania, Philadelphia, PA, USA). 21 Using this gene sequence data, 3C10-CAR cDNA was generated by gene synthesis (Genscript, Piscataway, NJ, USA). The mock vector was designed to harbor the scrambled sequence of the scFv portion that has shown no functional activity against glioma, breast cancer, colon cancer and pancreatic cancer cell lines.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene sequence data for the third-generation CAR was kindly provided by Dr Carl June (University of Pennsylvania, Philadelphia, PA, USA). 21 Using this gene sequence data, 3C10-CAR cDNA was generated by gene synthesis (Genscript, Piscataway, NJ, USA). The mock vector was designed to harbor the scrambled sequence of the scFv portion that has shown no functional activity against glioma, breast cancer, colon cancer and pancreatic cancer cell lines.…”
Section: Cell Linesmentioning
confidence: 99%
“…18,19 Further, we constructed human T cells that expressed chimeric antigen receptor (CAR) targeting the EGFRvIII antigen (3C10-CAR). 20,21 CARs are genetically constructed from scFvs connected by a transmembrane hinge region, the T-cell signaling complex, and costimulatory signaling domains (e.g. CD3ζ, CD28, 4-1BB and/or OX-40).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, it can take approximately 3-5 weeks to manufacture clinical-grade modified CAR T cells [78][79][80], depending on the genetic modification method used. The EGFRvIII and IL13Rα2 CAR T-cell therapies have shown efficacy in murine model systems of glioma and CNS melanoma [81][82][83][84], and these strategies, as well as HER2-CAR T cell therapy, are currently being investigated in GBM Phase I clinical trials (NCT02209376, NCT01454596, NCT02208362, NCT02442297, NCT01109095). However, this approach will require a portfolio of CARs and may also have treatment failures owing to antigenic loss/clonotypic selection.…”
Section: Gbm Immunotherapy and Precision Medicinementioning
confidence: 99%
“…At present, it was found that miR-153 inhibits IDO1 expression in cancer cells, and which is a tumor-suppressive miRNA that enhances CAR-T cell immunotherapy for solid tumors [86]. More importantly, the over-expression of the miR-17-92 cluster in CAR-transduced T cells results in prolonged protection against tumor re-challenge in a xenograft model of glioma, indicating the potential of engineered T cells with miRNAs for the treatment of cancer [87]. There are also studies demonstrating better antitumor responses and long-term persistence when both CD4 + and CD8 + CAR-T cells are transferred [88], and it has been proven that one critical role for miRNAs in CD4 + T cells is to help maintain the functional phenotypes of distinct T cell lineages [58].…”
Section: Integrating Mirnas Into the Design Of Future Immunotherapeutmentioning
confidence: 99%